Housing affordability of middle income households in Kuala Lumpur - Che Hassan, Intan Melati; Abdul Aziz, Faziawati; Abu Bakar, Nor Azlina; Ahmad, Noordin (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2019)
The housing price in Kuala Lumpur is more expensive than other areas in Malaysia. The mismatch between demand and supply is not due to lack of supply, but the constraint is on the supply of housing that can be accessed especially by the middle income households. Apart from housing price and household income, housing type is also a crucial factor that directly influences housing affordability in Kuala Lumpur. Terraced and high-rise houses are favoured and within affordable means of the middle income groups. Analysis of the housing price index for these two types in Kuala Lumpur plotted against Malaysia Housing Price Index (MHPI) from 2000 to 2016 portrayed that both exceeded the rate of MHPI with a higher value and sharper gradient in the terraced house index, signifying rapid increment in their values. Detail analysis was also carried out on these two types using Price to Income ratio method to calculate housing affordability. Kuala Lumpur seems to fall into the seriously to severely unaffordable household category at Price-Income ratios of 4.27 to 6.76 for terraced and highrise, respectively.